Ecological conditions during the Middle to Upper Palaeolithic transition (MIS 3) in Iberia: the cold‐adapted faunal remains from Mainea, northern Iberian Peninsula. (17th December 2020) - Rodríguez‐Almagro, Manuel; Sala, Nohemi; Wiβing, Christoph; Arriolabengoa, Martin; Etxeberria, Francisco; Rios‐Garaizar, Joseba; Gómez‐Olivencia, Asier
Abstract : Cold‐adapted faunal populations shifted southwards during the coldest episodes of the Middle and Late Pleistocene, reaching the Iberian Peninsula. In this context, some of these species, such as Coelodonta antiquitatis and Mammuthus primigenius extended throughout the territory, leaving evidence in, at least, 35 and 29 sites, respectively; however, in most cases, the evidence is scarce. Here we present the fossil assemblage from Mainea cave (Uitzi, Navarre, northern Iberian Peninsula), one of the sites yielding cold‐adapted faunal remains closer to the Pyrenees. The cave possibly acted as a natural trap due to its external geomorphology (a sinkhole) and the absence of aerial exposure, anthropogenic marks or evidence compatible with this site being a hyena den. This site has yielded the most evidence of Coelodonta antiquitatis remains (NISP = 190) and one of the most abundant in terms of number of individuals (five, each with different ages at death) for the Iberian Peninsula, five remains attributed to a single Mammuthus primigenius and a single Cervus elaphus remain. The direct dating of a woolly rhinoceros tooth (46 354–44 428 2σ cal. a BP) places Mainea within MIS 3, between the H4 and H5 Heinrich Events, during the Middle to Upper Palaeolithic transition, within a context of changes in human behaviour and human species replacement in Europe. We have performed the first collagen isotopic analysis for a woolly rhinoceros from the Iberian Peninsula. The δ 13 C and δ 15 N values of the Coelodonta antiquitatis remains are similar to other European sites, thus suggesting the presence of Mammoth steppe environments at relatively high altitudes, which would compensate for the southern latitude. This would be consistent with the presence of open environments in lower altitudes. This site expands our understanding of the ecology of cold‐adapted faunas at their furthest southern range limit during the Middle to Upper Palaeolithic transition.